Concentration Level and Market Power of Islamic Bank Industry: Analysis of Pre and Post Bank Syariah Indonesia Merger - Yaser Taufik Syamlan; Sari Wahyuni; Lily Sudiharto (Journal of Islamic Economic and Business Research, 2023)
This paper attempted to examine the concentration and the degree of market power in the Indonesian Islamic Bank Industry during the pre and post-Bank Syariah Indonesia mega-merger. However, using the Strategic Tripod concept, this paper explored the response of the competitor pursuant to the merger. This paper used two main secondary data sources, which were 2 quarterly financial reports before the merger and 1 quarterly financial report after the merger of 34 Islamic bank data, and applied the Herfindhal-Hircsmann Index and Concentration Ratio of the top 5 Islamic banks. This paper discovered that the concentration ratio was at a moderate level. Moreover, based on the CR5 calculation result, Islamic banks have an oligopoly market structure. As for the response to the mega-merger, this paper divides 34 islamic banks into 3 clusters which are full-fledged Islamic banks (Bank Umum Syariah), Private Owned Islamic Subsidiary (Unit Usaha Syariah), Province Owned Islamic Subsidiary (Unit Usaha Syariah Bank BPD). Based on the strategic tripod, the strategy of the Islamic full-fledged bank orchestrates resources to win the competition. The privately owned Islamic Subsidiaries are taking advantage of their resource sharing with their parents. Meanwhile, the Province Islamic subsidiary's strategy relies on the regulations determined by the bank shareholders, who, in this case, are the government province.